Laminated cell and intermediate connection layer and preparation method thereof
By introducing an intermediate connecting layer composed of an optical film or a filter film into the stacked battery, the incident light is divided into two parts: reflection and transmission, which solves the problem of "wave trough" in the stacked battery absorbing the sun's spectrum and improves the photoelectric conversion efficiency.
Patent Information
- Application Number
- CN202411843795.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-14
- Publication Date
- 2025-03-21
AI Technical Summary
The existing stacked batteries have "troughs" with low absorption intensity when absorbing the sun's spectrum, which makes some sunlight unable to be effectively utilized, thus limiting the photoelectric conversion efficiency of stacked batteries.
An intermediate connecting layer consisting of an optical film or a filter film is used. The filter film includes a multi-layer filter film and glass particles with a set particle size, which is used to divide the incident light into two parts, one part is reflected back to the upper cell, and the other part is transmitted to the adjacent narrow band gap battery to form a photocurrent.
By finely controlling the reflection and transmission of light, the reflection loss of light is reduced, ensuring that light of different wavelengths can be effectively absorbed by batteries with different band gaps, and improving the absorption range and photoelectric conversion efficiency of stacked batteries to the solar spectrum.
Smart Images

Figure CN119677295A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photovoltaic cells, and in particular to a stacked cell and an intermediate connecting layer thereof, and a preparation method thereof. Background Art
[0002] The structure of the stacked cell mainly consists of two parts: the upper cell and the lower cell. Generally speaking, the upper cell on the light-facing side has a larger band gap of light-absorbing materials, and is mainly responsible for absorbing the higher energy part of the spectrum of sunlight. The lower cell on the backlight side has a smaller band gap of light-absorbing materials, and mainly absorbs the lower energy part of the spectrum of sunlight transmitted from the upper cell. Through such a structural design, the energy conversion efficiency of the stacked cell to sunlight is improved.
[0003] However, there are absorption peaks at different positions in the absorption spectra of the upper and lower cells. Although this has broadened the absorption range of the stacked cells to a certain extent, due to the difference in the absorption peak positions, a "trough" of low absorption intensity is formed between the absorption peak positions of the upper and lower cells. This makes it impossible to effectively utilize part of the sunlight, which in turn limits the efficiency of the stacked cells. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a stacked cell and its intermediate connecting layer and a preparation method thereof in view of the deficiencies in the above-mentioned prior art, so as to solve the technical problem that the photoelectric conversion efficiency of the stacked cell is relatively low.
[0005] The objective of the present invention is achieved by the following technical solutions: In the first aspect, the present invention provides an intermediate connection layer of a stacked battery, which is composed of an optical film or a filter film. The optical film includes multiple layers of filter films and glass particles of a set particle size. The filter film is used to divide the received light into two parts, one part of the light is reflected back to the upper layer, and the other part of the light passes through the filter film to the adjacent narrow bandgap battery to form a photocurrent.
[0006] As a further improvement of the present invention, the filter film is an EVA film, a POE film, a PVB film or a co-extruded film, and photonic crystals or pearlescent powder pigments of different particle sizes are arranged in the film.
[0007] As a further improvement of the present invention, the photonic crystal is composed of silicon dioxide, polymethyl methacrylate balls and polystyrene balls of different particle sizes according to a set ratio.
[0008] As a further improvement of the present invention, the particle sizes of the silicon dioxide, polymethyl methacrylate spheres and polystyrene spheres are determined according to the set reflected light wavelength requirements, and the particle size setting range is between 100-1000 μm.
[0009] As a further improvement of the present invention, the thickness of the optical film or the filter adhesive film is set to 0.2-0.8 mm.
[0010] As a further improvement of the present invention, nanoparticles are further added to the filter adhesive film to fine-tune the refractive index of the intermediate connecting layer.
[0011] As a further improvement of the present invention, the optical film comprises at least two layers of filter films, the glass particles are arranged between the two layers of filter films, and the particle size of the glass particles is determined according to the set reflected light band and refracted light band.
[0012] In a second aspect, the present invention provides a laminated battery, comprising: An intermediate connecting layer, wherein the intermediate connecting layer is the connecting layer as described above; The bottom cell is used to connect to one side of the middle connection layer, receive the light signal of the light-transmitting middle connection layer, and form a photocurrent; The top cell is used to be connected to the side of the middle connection layer away from the bottom cell, and the top cell is used to convert the electrical signal into an optical signal transmitted to the middle connection layer, and receive the optical signal reflected by the middle connection layer to form a photocurrent.
[0013] As a further improvement of the present invention, the top cell is one of a perovskite cell, a donor acceptor cell, a cadmium telluride solar cell, a copper indium gallium selenide solar cell or a gallium arsenide solar cell.
[0014] In a third aspect, the present invention provides a method for preparing a laminated battery, which is used to prepare the above-mentioned laminated battery, comprising: Determine the band gap of the top cell and the band gap of the bottom cell; The set reflection band is determined according to the band gap of the top battery; Determine the particle size of particles in the optical film or filter film in the intermediate connection layer according to the set reflection band; The determined top battery, middle connection layer and bottom battery are connected in sequence to obtain a stacked battery.
[0015] The beneficial effects of the present invention are as follows: the intermediate connection layer of the stacked battery provided by the present invention, the filter film divides the incident light into two parts, one part is reflected back to the upper battery, and the other part passes through the filter film and enters the adjacent narrow bandgap battery. This design ensures that light of different wavelengths can be effectively absorbed by batteries with different band gaps. The light reflected back to the upper battery can be absorbed again, improving the utilization rate of the upper battery, and the transmitted light enters the narrow bandgap battery, further broadening the battery's absorption range of the solar spectrum. The stacked battery of the present invention can absorb energy in the solar spectrum more comprehensively, thereby improving the overall photoelectric conversion efficiency. The filter film reduces the reflection loss of light through fine control of reflection and transmission. The filter film reduces the reflection loss of light through fine control of reflection and transmission.
[0016] Furthermore, photonic crystals have a photonic bandgap structure that can selectively reflect or transmit light of a specific wavelength. By setting photonic crystals of different particle sizes in the film, the propagation path and reflection characteristics of light of different wavelengths can be precisely controlled. The photonic crystals enhance the ability to control light of a specific wavelength, allowing the stacked cells to more effectively utilize different parts of the solar spectrum and improve the photoelectric conversion efficiency. Pearlescent pigments have unique reflection and scattering properties that can scatter light of a specific wavelength and increase the path length of light in the cell. Through the scattering effect, pearlescent pigments can improve the absorption efficiency of light and reduce the reflection loss of light. Photonic crystals and pearlescent pigments reduce light loss and improve the overall efficiency of the cell.
[0017] Furthermore, silica, PMMA and PS have different refractive indices. By adjusting their ratio and particle size, a photonic band gap with a wide spectral range can be formed, which can effectively reflect or transmit light in a specific wavelength range, thereby precisely controlling the propagation path and spectral distribution of light. By designing different particle sizes and material ratios, photonic crystals can selectively reflect or transmit light of specific wavelengths, enhancing the absorption efficiency of light of specific wavelengths.
[0018] Furthermore, by adding different types and concentrations of nanoparticles (such as silicon dioxide, titanium dioxide, aluminum oxide, etc.) to the filter film, the refractive index of the film can be precisely adjusted, and the propagation path of light in the battery can be more controllable, thereby improving the utilization of light. The multiple scattering effect of nanoparticles can make the light evenly distributed in the battery, avoiding local light intensity being too high or too low.
[0019] Furthermore, in the laminated cell provided by the present invention, the filter film in the middle connecting layer divides the received light into two parts, one part of the light is reflected back to the top cell for reabsorption and utilization, and the other part of the light passes through the filter film and enters the bottom cell for generating photocurrent. Through this spectrum splitting mechanism, the laminated cell can more comprehensively utilize the different wavelengths of light in the solar spectrum, thereby improving the utilization rate of light and the photoelectric conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 Schematic diagram of the stacked battery structure in an embodiment of the present invention. DETAILED DESCRIPTION
[0022] In order to make the purpose and technical solution of the present invention clearer and easier to understand, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0023] The technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, wherein the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments.
[0024] Example 1 This embodiment provides an intermediate connection layer for a stacked battery. Figure 1 As shown, the middle connection layer of the stacked cell is composed of an optical film or a filter film. The optical film includes multiple layers of filter films and glass particles of a set particle size. The filter film is used to divide the received light into two parts, one part of the light is reflected back to the upper layer, and the other part of the light passes through the filter film to the adjacent narrow bandgap cell to form a photocurrent.
[0025] One side of the middle connecting layer of the stacked battery is used to connect the top battery, and the other side is used to connect the bottom battery. In this embodiment, the top battery is a wide bandgap battery, and the bottom battery is a narrow bandgap battery.
[0026] The filter film is an EVA (ethylene-vinyl acetate copolymer) film, POE (polyolefin elastomer) film or PVB (polyvinyl butyral) film or a co-extruded film prepared from an EVA film, POE film or PVB film, and photonic crystals or pearlescent powder pigments of different particle sizes are arranged in the film.
[0027] Among them, EVA film has good light transmittance, weather resistance and mechanical properties. POE film has excellent high temperature performance and weather resistance, and can maintain stable performance in high temperature environment. PVB film has good adhesion and optical properties. The co-extruded film combines different materials through the co-extrusion process to form a composite film with multiple functions. These materials themselves have good mechanical properties and flexibility, and can adapt to the deformation and stress changes of the battery in different use environments. It can improve the mechanical stability and reliability of the battery and extend the service life of the battery. Each type of film has corresponding advantages. The selection of film materials can be determined according to the actual application scenario of photovoltaic cells. In addition, these materials of EVA film, POE film or PVB film have good electrical insulation properties, which can effectively prevent the occurrence of internal short circuit or leakage of the battery.
[0028] In addition, photonic crystals or pearlescent pigments of different particle sizes are also arranged in these adhesive films. Photonic crystals have a photonic bandgap structure and can selectively reflect or transmit light of a specific wavelength. By arranging photonic crystals of different particle sizes in the adhesive film, the propagation path and reflection characteristics of light of different wavelengths can be accurately controlled. The control ability of light of a specific wavelength is enhanced by adding photonic crystals, so that the stacked cells can more effectively utilize different parts of the solar spectrum and improve the photoelectric conversion efficiency. Pearlescent pigments have unique reflection and scattering properties, which can scatter light of a specific wavelength and increase the path length of light in the battery. Through the scattering effect, pearlescent pigments can improve the absorption efficiency of light and reduce the reflection loss of light. Photonic crystals and pearlescent pigments of different particle sizes can adjust the reflection and transmission characteristics of light and reduce the reflection loss of light.
[0029] Photonic crystals are composed of silica (SiO2), polymethyl methacrylate (PMMA) balls and polystyrene (PS) balls of different particle sizes in a set ratio. Specifically, silica, PMMA and PS have different refractive indices. By adjusting their ratios and particle sizes, a photonic band gap with a wide spectral range can be formed. Photonic crystals can effectively reflect or transmit light in a specific wavelength range, thereby precisely controlling the propagation path and spectral distribution of light. By designing different particle sizes and material ratios, photonic crystals can selectively reflect or transmit light of specific wavelengths. The absorption efficiency of light of a specific wavelength is enhanced. For example, in a stacked cell, more light suitable for absorption by the lower cell can be transmitted, while reflecting back light suitable for absorption by the upper cell. Particles of different particle sizes can produce multiple scattering effects, increasing the path length of light in the cell. The probability of light absorption is increased, especially in the long wavelength region, where the light absorption efficiency is significantly improved.
[0030] Silica, polymethyl methacrylate balls and polystyrene balls are composed in a set ratio, and the particle size setting range is between 100-1000μm, which is determined according to the set reflected light wavelength. Particles of different particle sizes can produce multiple scattering effects, increase the path length of light in the battery, and improve the light absorption efficiency.
[0031] The particle size of the particles in the optical film or filter film in the intermediate connection layer is calculated and determined according to the set reflected light band:
[0032] in, is the wavelength of reflected light, D is the size of the microsphere, n is the refractive index, is the incident angle. The intermediate connection layer can improve the photoelectric conversion efficiency by 0.1~0.7% (absolute value).
[0033] This embodiment also adds nanoparticles to the filter film to fine-tune the refractive index of the intermediate connection layer. Commonly used nanoparticles include silicon dioxide (SiO2), titanium dioxide (TiO2), aluminum oxide (Al2O3), etc. By adjusting the refractive index of the filter film, the refraction and reflection characteristics of light can be optimized and the interface reflection loss can be reduced. Nanoparticles can scatter light of a specific wavelength, increase the path length of light in the battery, and improve the light absorption efficiency.
[0034] The optical film includes at least two layers of filter films. Glass particles are arranged between the two layers of filter films. The particle size of the glass particles is determined according to the set reflected light band and refracted light band. By adjusting the particle size, the scattering and transmission characteristics of light can be controlled.
[0035] When determining the thickness of an optical film or a filter film, it is necessary to consider the variation patterns of optical processes such as light absorption, scattering and reflection at different thicknesses. For example, if the film is too thin, it may not be able to effectively process the light, resulting in poor light regulation; and if the film is too thick, on the one hand, it may increase the propagation loss of light, and on the other hand, it may cause difficulties to the overall structure and manufacturing process of the battery. At the same time, the thickness also needs to match the size and distribution of other components such as photonic crystals and glass particles to achieve the best light management effect. The thickness of the optical film or filter film is set in the range of 0.2~0.8mm. Therefore, in this embodiment, the thickness of the optical film or filter film is set to 0.3mm.
[0036] Through the combination of filter film and glass particles, the incident light is carefully managed and the utilization rate of light is improved. At the same time, the reflection and scattering loss of light is reduced, and more light is effectively utilized.
[0037] Example 2 This embodiment provides a stacked battery, such as Figure 1 As shown, it mainly includes: an intermediate connection layer, a bottom battery and a top battery.
[0038] The intermediate connection layer is connected between the bottom battery and the top battery. The intermediate connection layer of the stacked battery is composed of an optical film or a filter film. The optical film includes multiple layers of filter films and glass particles of a set particle size. The filter film is used to divide the received light into two parts, one part of the light is reflected back to the upper layer, and the other part of the light passes through the filter film to the adjacent narrow bandgap battery to form a photocurrent.
[0039] One side of the middle connecting layer of the stacked battery is used to connect the top battery, and the other side is used to connect the bottom battery. In this embodiment, the top battery is a wide bandgap battery, and the bottom battery is a narrow bandgap battery.
[0040] The filter film is an EVA (ethylene-vinyl acetate copolymer) film, POE (polyolefin elastomer) film or PVB (polyvinyl butyral) film or a co-extruded film prepared from an EVA film, POE film or PVB film, and photonic crystals or pearlescent powder pigments of different particle sizes are arranged in the film.
[0041] Among them, EVA film has good light transmittance, weather resistance and mechanical properties. POE film has excellent high temperature performance and weather resistance, and can maintain stable performance in high temperature environment. PVB film has good adhesion and optical properties. The co-extruded film combines different materials through the co-extrusion process to form a composite film with multiple functions. These materials themselves have good mechanical properties and flexibility, and can adapt to the deformation and stress changes of the battery in different use environments. It can improve the mechanical stability and reliability of the battery and extend the service life of the battery. Each type of film has corresponding advantages. The selection of film materials can be determined according to the actual application scenario of photovoltaic cells. In addition, these materials of EVA film, POE film or PVB film have good electrical insulation properties, which can effectively prevent the occurrence of internal short circuit or leakage of the battery.
[0042] In addition, photonic crystals or pearlescent pigments of different particle sizes are also arranged in these adhesive films. Photonic crystals have a photonic bandgap structure and can selectively reflect or transmit light of a specific wavelength. By arranging photonic crystals of different particle sizes in the adhesive film, the propagation path and reflection characteristics of light of different wavelengths can be accurately controlled. The control ability of light of a specific wavelength is enhanced by adding photonic crystals, so that the stacked cells can more effectively utilize different parts of the solar spectrum and improve the photoelectric conversion efficiency. Pearlescent pigments have unique reflection and scattering properties, which can scatter light of a specific wavelength and increase the path length of light in the battery. Through the scattering effect, pearlescent pigments can improve the absorption efficiency of light and reduce the reflection loss of light. Photonic crystals and pearlescent pigments of different particle sizes can adjust the reflection and transmission characteristics of light and reduce the reflection loss of light.
[0043] Photonic crystals are composed of silica (SiO2), polymethyl methacrylate (PMMA) balls and polystyrene (PS) balls of different particle sizes in a set ratio. Specifically, silica, PMMA and PS have different refractive indices. By adjusting their ratios and particle sizes, a photonic band gap with a wide spectral range can be formed. Photonic crystals can effectively reflect or transmit light in a specific wavelength range, thereby precisely controlling the propagation path and spectral distribution of light. By designing different particle sizes and material ratios, photonic crystals can selectively reflect or transmit light of specific wavelengths. The absorption efficiency of light of a specific wavelength is enhanced. For example, in a stacked cell, more light suitable for absorption by the lower cell can be transmitted, while reflecting back light suitable for absorption by the upper cell. Particles of different particle sizes can produce multiple scattering effects, increasing the path length of light in the cell. The probability of light absorption is increased, especially in the long wavelength region, where the light absorption efficiency is significantly improved.
[0044] Silica, polymethyl methacrylate balls and polystyrene balls are composed in a set ratio, and the particle size setting range is between 100-1000μm, which is determined according to the reflected light wavelength set by the top battery. Particles of different particle sizes can produce multiple scattering effects, increase the path length of light in the battery, and improve the light absorption efficiency.
[0045] The particle size of the particles in the optical film or filter film in the middle connection layer is calculated and determined according to the reflected light band set by the top battery:
[0046] in, is the wavelength of reflected light, D is the size of the microsphere, n is the refractive index, is the incident angle. The intermediate connection layer can improve the photoelectric conversion efficiency by 0.1~0.7% (absolute value).
[0047] This embodiment also adds nanoparticles to the filter film to fine-tune the refractive index of the intermediate connection layer. Commonly used nanoparticles include silicon dioxide (SiO2), titanium dioxide (TiO2), aluminum oxide (Al2O3), etc. By adjusting the refractive index of the filter film, the refraction and reflection characteristics of light can be optimized and the interface reflection loss can be reduced. Nanoparticles can scatter light of a specific wavelength, increase the path length of light in the battery, and improve the light absorption efficiency.
[0048] The optical film includes at least two layers of filter films. Glass particles are arranged between the two layers of filter films. The particle size of the glass particles is determined according to the set reflected light band and refracted light band. By adjusting the particle size, the scattering and transmission characteristics of light can be controlled.
[0049] The bottom cell, most of which are narrow bandgap cells, receives the light signal from the light-transmitting middle connecting layer to form a photocurrent.
[0050] The top cell is used to connect to the side of the middle connection layer away from the bottom cell. Most of the top cells are wide-gap cells. The top cell is mainly used to convert electrical signals into optical signals transmitted to the middle connection layer, and receive optical signals reflected by the middle connection layer to form photocurrent. In this embodiment, the top cell band gap is set to 1.65eV and the bottom cell band gap is set to 1.12eV.
[0051] The wavelength corresponding to the band gap of the top cell is calculated by the following formula:
[0052] The reflected light band of the top cell band gap should be smaller than .
[0053] A part of it is reflected and re-enters the top wide band gap cell, and the reflected light is mainly visible light. The other part is transmitted into the bottom narrow band gap cell, but the transmitted light is mainly near-infrared light. These two parts of light can be quantitatively adjusted by changing the particle size of SiO2, PMMA or PS balls, thereby quantitatively adjusting the photocurrent of the top cell and the bottom cell.
[0054] Example 3 Based on the laminated battery described in Example 2, this embodiment provides a method for preparing a laminated battery. The method mainly includes: Determine the band gap of the top battery and the band gap of the bottom battery, such as the band gap of the top battery is 1.65eV and the band gap of the bottom battery is 1.12eV; The set reflected light band is determined according to the band gap of the top battery. The wavelength corresponding to the band gap of the top battery is calculated by the following formula:
[0055] The reflected light band of the top cell band gap should be smaller than ; The particle size of the particles in the optical film or filter film in the intermediate connecting layer is determined by calculating the particle size formula according to the set reflected light band. It should be understood that the above description of the preferred embodiment is relatively detailed and cannot be regarded as limiting the scope of protection of the patent of the present invention. Under the enlightenment of the present invention, ordinary technicians in this field can also make substitutions or deformations without departing from the scope of protection of the claims of the present invention, which all fall within the scope of protection of the present invention. The scope of protection requested for the present invention shall be based on the attached claims.
Claims
1. A laminated battery intermediate connection layer, characterized in that: It is composed of an optical film or a filter film, wherein the optical film includes multiple layers of filter films and glass particles of set particle size. The filter film is used to divide the received light into two parts, one part of the light is reflected back to the upper layer, and the other part of the light passes through the filter film to the adjacent narrow bandgap battery to form a photocurrent.
2. The intermediate connection layer of the laminated battery according to claim 1, characterized in that: The filter film is an EVA film, a POE film, a PVB film or a co-extruded film, and photonic crystals or pearlescent powder pigments with different particle sizes are arranged in the film.
3. The intermediate connection layer of the laminated battery according to claim 2, characterized in that: The photonic crystal is composed of silicon dioxide, polymethyl methacrylate balls and polystyrene balls of different particle sizes according to a set ratio.
4. The intermediate connection layer of the laminated battery according to claim 3, characterized in that: The particle sizes of the silicon dioxide, polymethyl methacrylate balls and polystyrene balls are determined according to the set wavelength of the reflected light, and the particle size setting range is between 100-1000 μm.
5. The intermediate connection layer of the laminated battery according to claim 2, characterized in that: The thickness of the optical film or filter film is set to 0.2~0.8mm.
6. The intermediate connection layer of the laminated battery according to claim 2 or 4, characterized in that: Nanoparticles are also added to the filter film to fine-tune the refractive index of the intermediate connection layer.
7. The intermediate connection layer of the laminated battery according to claim 1, characterized in that: The optical film comprises at least two layers of filter films, and the glass particles are arranged between the two layers of filter films. The particle size of the glass particles is determined according to the set reflected light band and refracted light band.
8. A laminated battery, characterized in that: include: An intermediate connecting layer, wherein the intermediate connecting layer is a connecting layer as claimed in any one of claims 1 to 6; The bottom cell is used to connect to one side of the middle connection layer, receive the light signal of the light-transmitting middle connection layer, and form a photocurrent; The top cell is used to be connected to the side of the middle connection layer away from the bottom cell, and the top cell is used to convert the electrical signal into an optical signal transmitted to the middle connection layer, and receive the optical signal reflected by the middle connection layer to form a photocurrent.
9. The laminated battery according to claim 8, characterized in that: The top cell is one of a perovskite cell, a donor acceptor cell, a cadmium telluride solar cell, a copper indium gallium selenide solar cell or a gallium arsenide solar cell.
10. A method for preparing a laminated battery, used for preparing the laminated battery according to claim 7, characterized in that: include: Determine the band gap of the top cell and the band gap of the bottom cell; The set reflection band is determined according to the band gap of the top battery; Determine the particle size of particles in the optical film or filter film in the intermediate connection layer according to the set reflection band; The determined top battery, middle connection layer and bottom battery are connected in sequence to obtain a stacked battery.
Citation Information
Patent Citations
Two-sided solar cell and manufacturing method thereof
CN103972313A
Photonic crystal heterojunction-based trans-form low-dimensional perovskite solar cell
CN112670415A
Photon EVA packaging adhesive film and preparation method thereof
CN116376472A
Amorphous / microcrystalline silicon laminated thin-film solar cell
CN202930415U